Critical criminology and literary criticism - McGregor, Rafe (Bristol University Press, 2022)
Establishing a new interdisciplinary methodology, 'criminological criticism', Rafe McGregor proposes a model for collaboration between literary studies and critical criminology that is beneficial to the humanities, the social sciences and society.